2022
DOI: 10.1002/jee.20455
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of future careers for middle year engineering students

Abstract: Background One facet of motivation relevant to students' learning is their perceptions of the future, including future career goals and how those perceptions influence their present actions; this is collectively referred to as their future time perspective (FTP). Purpose/Hypothesis This study describes the different FTPs of engineering students. We aim to help researchers and practitioners leverage students' motivations to improve learning experiences and inform future studies by providing a model of engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…The theory posits that students' ability to make connections between their present actions and future goals, particularly their ability to identify and pursue steps that will lead them to successful goal attainment, leads to stronger motivation for success. Within engineering, researchers have found that students' FTPs differ and that those differences can be linked to varying levels of academic success [10]. Current FTP research in engineering suggests that students who have more defined FTPs are more likely to see the steps they need to be successful and to find relevance between what they are doing now with their future.…”
Section: Introductionmentioning
confidence: 99%
“…The theory posits that students' ability to make connections between their present actions and future goals, particularly their ability to identify and pursue steps that will lead them to successful goal attainment, leads to stronger motivation for success. Within engineering, researchers have found that students' FTPs differ and that those differences can be linked to varying levels of academic success [10]. Current FTP research in engineering suggests that students who have more defined FTPs are more likely to see the steps they need to be successful and to find relevance between what they are doing now with their future.…”
Section: Introductionmentioning
confidence: 99%